MAKNA AJARAN BRAHMAWIDYĀ DALAM TATTWA SANGHYANG MAHĀJÑĀNA - Ida Made Windya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Tattwa Sanghyang Mahājñāna is one of the Śiwa tattwa’s scripture, which teaches aboutātma jñana (knowledge of one's own nature) to achieve kalêpasan through the path of jñana sandhi(yogic knowledge). There has been no research on the meaning of Brahmawidyā teachings in theTattwa Sanghyang Mahājñāna, so research is needed. Besides that no one has researched it, it isalso considered the Tattwa Sanghyang Mahājñāna as an old and complete text as a source ofBrahmawidyā teachings, especially Úiwa Siddhānta. This study aims to determine the meaning ofBrahmawidyā teachings in the Tattwa Sanghyang Mahājñāna. To analyze the meaning of theteachings, the hermeneutic theory is used, so that it is easy to understand according to the currentcontext. The method used in this research is a literature study with a qualitative research typeapproach. The results of the study found several meanings, including: 1) The meaning of selfcontrol, explaining the ability or effort to control materialistic elements that can affect the qualityof the soul. 2) The meaning of surrender to God (Īśwarapranidhāna), explains the form of effortin getting closer to Lord Śiwa. 3) The meaning of spiritual awareness, explains the awareness thatis achieved by the soul and is not trapped in material or worldly elements. 4) The meaning ofliberation, namely the detachment from the world which in the context of Hinduism is called mokṣaor kalêpasan